2021
DOI: 10.1161/jaha.121.022984
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Impact of Intraprocedural Stent Thrombosis During Percutaneous Coronary Intervention in Patients Treated With Potent P2Y12 inhibitors ‐ a VALIDATE‐SWEDEHEART Substudy

Abstract: Background The clinical importance of intraprocedural stent thrombosis (IPST) during percutaneous coronary intervention in the contemporary era of potent oral P2Y12 inhibitors is not established. The aim of this study was to assess IPST and its association with clinical outcome in patients with myocardial infarction undergoing percutaneous coronary intervention with contemporary antithromboticmedications. Methods and Results The VALIDATE‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Despite these advancements, the pathophysiological underpinnings of ST remain elusive, with factors such as lesion morphology, adherence to dual antiplatelet therapy (DAPT), diabetes prevalence, and stent design emerging as significant contributors. The heterogeneity observed in histopathological analyses of thrombus specimens further complicates the understanding of ST, with a diverse array of components such as platelet-rich clots and fibrin/fibrinogen fragments being implicated (2,3,14). Our investigation aligns with existing literature, highlighting a mortality rate of 24% in patients undergoing primary PCI for STEMI attributed to ST, a figure that resonates with findings from other studies within the Pakistani context, which have reported similar mortality rates post-PCI.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Despite these advancements, the pathophysiological underpinnings of ST remain elusive, with factors such as lesion morphology, adherence to dual antiplatelet therapy (DAPT), diabetes prevalence, and stent design emerging as significant contributors. The heterogeneity observed in histopathological analyses of thrombus specimens further complicates the understanding of ST, with a diverse array of components such as platelet-rich clots and fibrin/fibrinogen fragments being implicated (2,3,14). Our investigation aligns with existing literature, highlighting a mortality rate of 24% in patients undergoing primary PCI for STEMI attributed to ST, a figure that resonates with findings from other studies within the Pakistani context, which have reported similar mortality rates post-PCI.…”
Section: Discussionsupporting
confidence: 85%
“…This adverse event can occur at any point following stent deployment, ranging from the immediate peri-procedural period to several years post-implantation. The rising prevalence of PCI as a therapeutic strategy has shifted the focus from procedural success towards the prevention of in-stent thrombosis (3,4). The advent of drug-eluting stents (DES) was initially heralded as a breakthrough in reducing the rate of restenosis observed with bare metal stents (BMS).…”
Section: Introductionmentioning
confidence: 99%